The influence of low-energy proton irradiaiton on threshold voltage and tranconductance of nanowire SOI n and p-channel transistors - Teixeira, Fernando F.; Agopian, Paula G. D. [UNESP]; Barraud, Sylvain; Vinet, Maud; Faynot, Olivier; Martino, Joao A. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
The goal of this work is analyze for the first time the low-energy proton irradiation elfects on p and n-channel SOI Ω-Gate Nanowire transistors for total ionization dose of 500 krad. After radiation, it is noticed a slight variation on a drain current and in a transconductance, for large devices, due to the back leakage current.
Keywords: back leakage current; Nanowire; oxide charger; proton irradiation